The Role of Curiosity in Academic Outcomes: A Study of Junior High School Science Students - Fadillah*, Rofi Wafa; Rahmat, Adi; Winarno, Nanang; Hanif, Norfazrin Mohd (Universitas Syiah Kuala, 2025)
In contemporary education, fostering curiosity in science learning is essential for enhancing students academic performance, particulary in junior high school. This study aims to explore the relationship between students curiosity in science learning and their learning outcomes in junior high school, focusing on three dimensions of curiosity: Stretching, Science, and Embrace. A correlational quantitative approach was employed, involving 147 students, with data collected through questionnaires, learning outcome assessments, and interviews. The results indicated that curiosity plays a role in improving learning outcomes, as evidenced by the average scores increasing from grade 7 (82.2) to grade 9 (85.8), influenced by the interactive teaching approach. However, despite an average curiosity score of 66.52, the correlation between the dimensions of curiosity and learning outcomes was found to be very weak (p 0.05), highlighting the need for more innovative learning strategies to effectively harness curiosity in the classroom